2022
DOI: 10.1371/journal.pgph.0000118
|View full text |Cite
|
Sign up to set email alerts
|

Non-communicable diseases attributed mortality and associated sociodemographic factors in Papua New Guinea: Evidence from the Comprehensive Health and Epidemiological Surveillance System

Abstract: Background Papua New Guinea (PNG) is undergoing an epidemiological transition with increased mortality from NCDs. This study examined NCDs-attributed mortality and associated sociodemographic factors in PNG. Method Using WHO 2016 instrument, 926 verbal autopsy (VA) interviews were conducted in six major provinces from January 2018 to December 2020. InterVA-5 tool was used to assign causes of death (COD). Multivariable logistic regression analysis was performed to identify sociodemographic factors associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…species and nitric oxide production in zebra fsh (LD 50 ) [99]. Toxicity studies with zingerone (5) and gingerol (6) have shown that they are safe [100,104].…”
Section: Zingiber Ofcinalementioning
confidence: 99%
See 2 more Smart Citations
“…species and nitric oxide production in zebra fsh (LD 50 ) [99]. Toxicity studies with zingerone (5) and gingerol (6) have shown that they are safe [100,104].…”
Section: Zingiber Ofcinalementioning
confidence: 99%
“…Accordingly, three in fve of the global deaths are ascribed to at least one of the four main noncommunicable diseases (NCDs), namely, cancer, diabetes, cardiovascular, and chronic lung diseases [3][4][5]. Most global mortalities (up to 71%) are due to NCDs [6], and 77% of these occur in low-and middle-income countries due to limited access to medical services and poverty [7]. Whereas the global focus is on the major NCDs, conditions such as sexual dysfunction, infertility, and anaphrodisia (sexual inappetence) represent some of the complex health challenges.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the household characteristics and assets from the household data as a proxy to evaluate socioeconomic status [19,38,44,45], a household wealth index was calculated using principal component analysis [46], The household wealth index was divided into five quintiles, with each quintile, from the first to the fifth, including the lowest or poorest household, lower or poorer households, middle households, higher or wealthier households, and highest or richest households [44,46]. Further information on similar analysis involving the surveillance data are discussed elsewhere [44,45,47,48].…”
Section: Measurementsmentioning
confidence: 99%